2021
DOI: 10.4081/ijfs.2021.9341
|View full text |Cite
|
Sign up to set email alerts
|

Identification and serotyping of <em>Listeria monocytogenes</em>, isolated from various salmon products, sold in retail market in Lithuania

Abstract: Cold smoked salmon products (belly flaps, pieces, fillet, and loin) obtained from the retail market in Lithuania were tested for the presence of L. monocytogenes. It was found that contamination of the cold smoked fish products with Listeria spp. depends on the type of the product. Contamination with listeria in salmon belly flaps was 7.5 times higher than in the loin (P<0.05), 1.8 times higher than in the pieces (P<0.05) and 30 times higher than in the fillet (P<0.05). Microbiological analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In contrast to the aforementioned reports in which the IIa serogroup was the most common among isolates, Simonavičienė et al [20], who used the protocol of Doumith et al [9], have found that the IVb segrogroup was the most prevalent in cold smoked fish (salmon) products from Lithuania. Out of 37 L. monocytogenes isolates, 35 (90.5 %) belonged to the IVb serogroup, whereas only 2 samples (5.4 %) were identified as members of the IIa serogroup [20]. However, these results are also in agreement with our findings, as only one serogroup, namely IVb, was identified in all 10 samples originating from smoked fish included in our study.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast to the aforementioned reports in which the IIa serogroup was the most common among isolates, Simonavičienė et al [20], who used the protocol of Doumith et al [9], have found that the IVb segrogroup was the most prevalent in cold smoked fish (salmon) products from Lithuania. Out of 37 L. monocytogenes isolates, 35 (90.5 %) belonged to the IVb serogroup, whereas only 2 samples (5.4 %) were identified as members of the IIa serogroup [20]. However, these results are also in agreement with our findings, as only one serogroup, namely IVb, was identified in all 10 samples originating from smoked fish included in our study.…”
Section: Resultsmentioning
confidence: 84%
“…Currently, there are 14 known serotypes (marked with the following symbols: 1/2a, 1/2b, 1/2c, 3a, 3b, 3c, 4a, 4ab, 4b, 4c, 4d, 4e, 7, 4h) [9,23], but only four of them (namely 4b, 1/2a, 1/2b, 1/2c) cause more than 95 % listerial cases and comprise more than 95 % isolates from food products [9]. Interestingly, the 1/2a isolate is the most frequently isolated from food, whereas the 4b serotype is responsible for the majority of infections [3,20].…”
Section: Introductionmentioning
confidence: 99%
“…Serogroups IIb and IVb have been previously identified in salmon sector [ 27 , 29 ]. Serogroup IIb has already been detected in rainbow trout from fish farms in lakes and sea areas around Finland [ 32 ], and several authors have reported a prevalent presence of serogroup IVb in the trout industry [ [33] , [34] , [35] ]. Serogroup IVb, particularlyserotype 4b, is known to be frequently associated with clinical cases of listeriosis.…”
Section: Resultsmentioning
confidence: 99%
“…The food-borne pathogenic bacteria such as Aeromonas hydrophilla, Bacillus cereus, Escherichia coli, Listeria monocytogenes, Salmonella Typhimurium, Staphylococcus aureus, Vibrio parahaemolyticus has been detected in various food and food products (Budiati et al, 2016, Simonavičienė et al, 2021. Currently, there is a need to develop antimicrobial to maintain food safety that meets the needs of consumers in natural and safe food products.…”
Section: Introductionmentioning
confidence: 99%